The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1103/physrevlett.89.225002
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Generated Ultrashort Multimegagauss Magnetic Pulses in Plasmas

Abstract: We demonstrate ultrashort (6 ps), multi-Megagauss (27 MG) magnetic pulses generated upon interaction of an intense laser pulse (10 16 Wcm −2 , 100 fs) with a solid target. The temporal evolution of these giant fields generated near the high density critical layer is obtained with the highest resolution reported so far. Particle-in-cell simulations and phenomenological modeling is used to explain the results. The first direct observations of anomalously rapid damping of plasma shielding currents produced in res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 33 publications
(26 reference statements)
0
50
1
Order By: Relevance
“…The magnetic field increases from 0 to 63 megagauss in 3.2 ps at the critical surface of the probe (400 nm) and starts decreasing beyond this time. Magnetic field strength is along expected lines (1,2,(15)(16)(17). Fig.…”
Section: Magnetic Field: Temporal and Spatial Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnetic field increases from 0 to 63 megagauss in 3.2 ps at the critical surface of the probe (400 nm) and starts decreasing beyond this time. Magnetic field strength is along expected lines (1,2,(15)(16)(17). Fig.…”
Section: Magnetic Field: Temporal and Spatial Profilesmentioning
confidence: 99%
“…A major physical parameter that mirrors this complex physics is the giant magnetic field-as high as hundreds of megagauss-generated in this interaction. In earlier studies (15)(16)(17), we have shown that the temporal evolution of this megagauss magnetic field can provide essential and very useful information on the transport processfor instance, the conductivity of the hot, dense matter and the penetration depth of the hot electrons can be estimated easily.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The study of SGMF and the knowledge of the plasma density in sub-ps pulse duration is important from point of view of energy transport by the laser pulse in the fast ignition regime [5,6]. SGMF in plasmas produced by sub-ps laser pulses has been measured by Cotton Mouton polarimetry in the sub-ps time scales [7,8] using the pump-probe method. However, one does not get information about the plasma density in these measurements done by using only one probe beam.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Understanding and controlling electromagnetic (EM) turbulence in these environments is critical to the studies in the fusion energy sciences, and for the inertial confinement concept, 6,7 in particular. Additionally, electromagnetic turbulence is a crucial aspect of numerous astrophysical systems such as gamma-ray bursts and supernova shocks.…”
Section: Introductionmentioning
confidence: 99%